Evaluation and associated risk factors for neutropenia with venetoclax and obinutuzumab in the treatment of chronic lymphocytic leukemia. Issue 5 (12th July 2021) - Samuels, Courtney; Abbott, Diana; Niemiec, Sierra; Tobin, Jennifer; Falco, Angela; Halsema, Keri; Kamdar, Manali
Abstract: Background: The time‐limited combination of venetoclax and obinutuzumab (VenG) was established by the German CLL Study Group in the CLL14 trial for the upfront management of newly diagnosed chronic lymphocytic leukemia (CLL), showing a superior progression free survival benefit. The incidence of grade 3–4 neutropenia was reported in the range of 52.8%–57.7%. However, patients who develop neutropenia with this combination have yet to be formally characterized in the literature as it has impact on the clinical practice setting. Aim: To determine the incidence of grade 3 and 4 neutropenia and identify risk factors for neutropenia among CLL patients treated with the VenG regimen. Methods: We conducted a retrospective, single‐center study of all adult patients with a diagnosis of CLL treated with VenG at the University of Colorado Hospital. Demographic information, laboratory data, clinical data, and medication prescriptions were collected from the patients' electronic medical record. Results: A total of 14 patients (73%) developed neutropenia during the course of therapy. The mean time to neutropenia from the start of treatment was 42 days (range 1–131). Our cohort harbored more high risk disease features and more comorbidities (CIRS score of 12). Four patients (28.6%) in the neutropenic group developed infectious complications during therapy and 6 (31%) patients were unable to be dose escalated to the final FDA approved dose of 400 mg. Conclusion: Our study cohort had higher incidence of grade 3 and 4 neutropenia occurring in 73% of patients. This could be attributed to a higher rate of comorbidities, high risk features, concomitant interacting medications, and prior chemotherapy. Further studies are warranted to determine if growth factor support is efficacious to achieve dose escalation with this therapy.